Long‐term exposure to increasing temperature can offset predicted losses in marine food quality (fatty acids) caused by ocean warming. (28th July 2020) - Jin, Peng; Gonzàlez, Gala; Agustí, Susana
Abstract: Marine phytoplankton produce essential fatty acids (FA), which are key component of a healthy diet in humans and marine food webs. Increased temperatures can reduce lipid and FA content in phytoplankton; thus, ocean warming poses a risk for the global production of these essential FA. However, responses to warming may differ between phytoplankton species especially after long‐term exposure because phenotypic plasticity, de novo mutations, or genetic evolution may occur. Here, we examine the content of FA and lipids in phytoplankton following long‐term selection ( 2 years) to warming conditions (+4°C), and we observe that FA and lipids content were partly or entirely recovered following long‐term exposure to warming conditions. Furthermore, this observed long‐term response also offset the predicted losses of some essential polyunsaturated fatty acids (PUFA) in three of the four species tested. Our study suggests that long‐term exposure of phytoplankton to warming may help to maintain marine food quality in a moderately warming ocean. The responses of FA to increasing temperatures may vary among species, and the level of this idiosyncrasy remains to be further studied.